ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TENGKAT KEPUASAN PENGUNJUNG TAMAN REKREASI DI PROPINSI RIAU (SURVEY ALAM MAYANG, DANAU BUATAN, KASANG KULIM, RINDU SEMPADAN) - Lusan Marini Putri; Zulkarnaini Zulkarnaini; Suardi Tarumun (Program Pascasarjana Universitas Riau, 2008)
A tourism is not a new business, particularly the tourism using the nature resources combined with playingpark, forestry park etc., that completed with all facilities needed by visitor. Thus, writer interest to conduct theresearch about satisfaction pf visitor to consumpt the nature tourisms or usually defined as ecotourism .Theresearch had used survey method to recreational park locations directly, such as Alam Mayang, Danau Buatan,Kasang Kulim dan Rindu Sempadan. Data analyzed by “Dummy Regresion by Dependent Variable, Logic”.The result is the factors had influenced the satisfactions of recreational parks (Alam Mayang, Danau Buatan,Kasang Kulim dan Rindu Sempadan), respectively, which of the visitor’s satisfactions to Alam Mayang forservices 4.159; for situation and condition of park 5.951; for sanitation 6.105 and for sacrificy 4.159; withconstant value -16.214. Then, the visitor’s satisfactions at Danau Buatan were for services 3.885; for situationand condition 6.862; for sanitation 6.386; and for sacrificy 2.086, with constant value -11.550. At KasangKulim, for services 22.687; for situation and condition 39.057; for sanitation 5.694; and for sacrificy 17.56,with constant value -60.871. At Rindu Sempadan, for services 3.396; for situation and condition 3.793; forsanitation 3.401; and for sacrificy 3.471, with constant value -9.735.